Matrix effect in matrix‐assisted laser desorption/ionization mass spectra of derivatized oligomeric polyols. (13th December 2012) - Borisov, Roman S.; Polovkov, Nikolai Yu.; Zhilyaev, Dmitry I.; Zaikin, Vladimir G.
<x xml:space="preserve">Abstract</x> RATIONALE Herein we describe a strong matrix effect observed in the matrix‐assisted laser desorption/ionization time‐of‐flight (MALDI‐ToF) mass spectra of silylated glycerol alkoxylates and manifested in the loss of the silyl groups in the presence of carboxyl‐containing matrices. METHODS Commercially available glycerol alkoxylates containing three end OH groups as well as three matrices – 2, 5‐dihydroxybenzoic acid (DHB), 3‐indoleacrylic acid (IAA) and 1, 8, 9‐anthracenetriol (dithranol) – were chosen for the investigation. N, O‐Bis(trimethylsilyl)trifluoroacetamide containing 1% trimethylchlorosilane, acetic anhydride and a formylation mixture (formic acid/acetyl chloride) were used for derivatization. Initial oligomers and derivatized products were analyzed by MALDI‐ToF‐mass spectrometry (MS) on an Autoflex II instrument, equipped with a nitrogen laser (λ 337 nm), in positive ion reflectron mode. RESULTS Only [M + Na]+ ions were observed for underivatized polymers and for completely derivatized polymers in the presence of DHB and dithranol, respectively. In the case of IAA the mass spectra revealed sets of peaks for underivatized, and for partially and completely derivatized oligomers. No similar 'matrix effect' was observed in the case of acylated glycerol alkoxylates (acyl = formyl, acetyl): only peaks for completely derivatized oligomers were obtained in all matrices: DHB, IAA and dithranol. Using 1, 9‐nonandiol, we showed that the 'matrix effect' was due to trans‐silylation of carboxyl‐containing matrices (DHB and IAA) during co‐crystallization of silylated oligomers and matrices. CONCLUSIONS The obtained results show that matrix molecules can participate as reactive species in MALDI‐ToF‐MS experiments. The matrix should be carefully chosen when a derivatization approach is applied because the analysis of spectra of the completely derivatized products is particularly desirable in the quantitative determination of functional end‐groups. Copyright © 2012 John Wiley & Sons, Ltd.